2023
DOI: 10.3389/fimmu.2023.1112257
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo test to investigate genetic factors conferring susceptibility to atypical haemolytic uremic syndrome

Abstract: IntroductionComprehensive genetic analysis is essential to clinical care of patients with atypical haemolytic uremic syndrome (aHUS) to reinforce diagnosis, and to guide treatment. However, the characterization of complement gene variants remains challenging owing to the complexity of functional studies with mutant proteins. This study was designed: 1) To identify a tool for rapid functional determination of complement gene variants; 2) To uncover inherited complement dysregulation in aHUS patients who do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We have no easy explanation of these findings, which are in contrast to the literature data, suggesting that a positive test on activated endothelium allows to detect patients with a genetic predisposition to aHUS. 14 All but 1 patient had a C3 mutation. Interestingly, the association between a positive test on activated endothelium and carriership of an aHUS genetic mutation might be dependent on polymorphisms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have no easy explanation of these findings, which are in contrast to the literature data, suggesting that a positive test on activated endothelium allows to detect patients with a genetic predisposition to aHUS. 14 All but 1 patient had a C3 mutation. Interestingly, the association between a positive test on activated endothelium and carriership of an aHUS genetic mutation might be dependent on polymorphisms.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it was suggested that a positive assay was found in carriers of an MCP mutation, but only in individuals who concomitantly were carriers of at least 1 CFH risk haplotype. 13 , 14 Further studies are needed to assess which factors influence the ex vivo endothelial test results: genetic variants, risk haplotypes, and/or other (yet unknown) factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous studies reported in the literature. The capability of the ex vivo C5b-9 formation assay to evaluate the presence of factors in serum that augment complement activation on endothelial cells, and to identify patients with TMA caused by complement dysregulation is in fact supported by several publications from different independent groups, including Giuseppe Remuzzi in Bergamo, 2 , 3 S.A.M.E.G. Timmermans in Maastricht 4 , 5 and Marta Palomo in Barcelona.…”
mentioning
confidence: 93%
“…Two principal techniques for in vitro diagnosis have been proposed, including the modified Ham assay (mHam) 9,10 and HMEC-1 staining for C5b-9 [11][12][13][14] , but neither is widely adopted. Both assays rely upon testing patient serum for abnormal cell-deposited complement activity.…”
Section: Introductionmentioning
confidence: 99%